2018
DOI: 10.1016/j.ekir.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis and Nephrocalcinosis From Topiramate Therapy in Children With Epilepsy

Abstract: IntroductionAdults treated with topiramate may develop nephrolithiasis, but its frequency in children on topiramate is unknown. Topiramate inhibits renal carbonic anhydrase, which can lead to renal tubular acidosis and hypercalciuria. We studied 40 consecutive children who initiated topiramate therapy for seizures between January 1997 and February 2003, followed for a mean of 36 months.MethodsSerum electrolytes, urinary calcium/creatinine ratios, and renal ultrasonography were performed before topiramate and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
1
0
2
Order By: Relevance
“…Otros fármacos como los corticoides o el topiramato, se asocian con nefrocalcinosis, sobre todo en edad pediátrica. También, existen varios casos en la literatura científica que hablan de la relación entre el fracaso renal agudo, hiperfosfaturia severa, y nefrocalcinosis y la toma de preparaciones intestinales de fosfato sódico para procedimientos endoscópicos o cirugías intestinales [2,8,12,13,17,21]. Posiblemente los mecanismos implicados en el desarrollo de la nefrocalcinosis tras el consumo de estos fármacos son la producción de alteraciones metabólicas similares a las que aparecen en la acidosis tubular renal distal tipo 1, dando lugar a una acidificación de la orina por la reabsorción residual de bicarbonato, provocándose un estado de hipocitraturia que favorece la formación de depósitos de fosfato cálcico [12,13,[21][22][23].…”
Section: Etiopatogeniaunclassified
“…Otros fármacos como los corticoides o el topiramato, se asocian con nefrocalcinosis, sobre todo en edad pediátrica. También, existen varios casos en la literatura científica que hablan de la relación entre el fracaso renal agudo, hiperfosfaturia severa, y nefrocalcinosis y la toma de preparaciones intestinales de fosfato sódico para procedimientos endoscópicos o cirugías intestinales [2,8,12,13,17,21]. Posiblemente los mecanismos implicados en el desarrollo de la nefrocalcinosis tras el consumo de estos fármacos son la producción de alteraciones metabólicas similares a las que aparecen en la acidosis tubular renal distal tipo 1, dando lugar a una acidificación de la orina por la reabsorción residual de bicarbonato, provocándose un estado de hipocitraturia que favorece la formación de depósitos de fosfato cálcico [12,13,[21][22][23].…”
Section: Etiopatogeniaunclassified
“…Thus, TPM has become one of the most frequently prescribed drugs in the USA, ranking among the top 50 most prescribed drugs [85]. TPM has been long known for its lithogenic effect through the metabolic changes induced by this drug [86][87][88][89][90][91][92][93]. A systematic review published in 2013 showed that the overall annual incidence of symptomatic nephrolithiasis with TPM usage was 2.1% [94]; however, the incidence of nephrolithiasis in the pediatric population ranged from 4.2% to 60% (Table 3).…”
Section: Topiramatementioning
confidence: 99%
“…Dentre os efeitos adversos manifestados em pacientes que fazem uso do Topiramato à longo prazo, pode-se mencionar a nefrolitíase. A estrutura do TPM é semelhante à do fármaco acetazolamida, visto que ambos possuem a função de inibir a anidrase carbônica, efeito que promove falha na reabsorção de bicarbonato, que causa alcalinização da urina e leva a um quadro de supersaturação de fosfato de cálcio e nefrolitíase [6]. O objetivo dessa revisão de literatura é procurar identificar estudos, em determinados bancos de dados, que evidenciem a incidência de cálculos renais nos indivíduos das diversas faixas etárias que realizam terapia com TPM à longo prazo, além de comparar os estudos mais antigos com os atuais relacionados a esse assunto.…”
Section: Introductionunclassified